Insight into the cryopolymerization to form a poly(N-isopropylacrylamide)/clay macroporous gel: structure and phase evolution - Strachota, Beata; Matějka, Libor; Sikora, Antonín; Spěváček, Jiří; Konefał, Rafał; Zhigunov, Alexander; Šlouf, Miroslav (Soft matter, 2017)
The cryopolymerization and formation of a macroporous poly(N-isopropylacrylamide) (PNIPA)/clay cryogel were investigated. The mechanism of the cryopolymerization and cryogel formation was elucidated. Two processes, cryostructuration and cryopolymerization, proceed simultaneously and their relative rates determine the structure evolution and the cryogel morphology - porosity. The cryostructuration in the PNIPA/clay system during freezing, controlled by the freezing temperature and the rate of cooling, includes both water and NIPA crystallization, formation of a highly concentrated non-frozen liquid phase (NFLP) and clay aggregation. The rate of cryopolymerization and gelation is governed by the following effects: by a low polymerization temperature and after freezing, by the high cryoconcentration and a steric confinement, manifested by a reduced reagent mobility. Moreover, it depends on the cooling rate and the evolution of cryostructuration. The progress of cryostructuration and cryopolymerization during freezing was described and experimentally proved step by step. Both the phase development during freezing and the progress of cryopolymerization including gelation were monitored in situ by NMR, DSC, chemorheology and SAXS. The morphology and porosity of the cryogels were characterized by SEM and TEM.